mRNA Processing: An Emerging Frontier in the Regulation of Pancreatic β Cell Function - Moss, Nicole D.; Sussel, Lori (Frontiers in Genetics, 2020)
Robust endocrine cell function, particularly β cell function, is required to maintain blood glucose homeostasis. Loss or damage of the β cell populations in the pancreas results in diabetes. Despite decades of clinical and basic research, the precise regulation of β cell function and pathogenesis in diabetes remains incompletely understood. In this review, we highlight RNA processing as a rapidly emerging mechanism regulating β cell function and survival. RNA-binding proteins (RBPs) and RNA modifications are primed to be the next frontier to explain many of the poorly understood regulatory processes that regulate β cell formation, function, and provide an exciting potential for the development of novel therapeutics. Here we outline current understanding β cell specific functions of several characterized RBPs, alternative splicing events, and transcriptome wide changes in RNA methylation. We also highlight the remaining gaps in knowledge, identifying several RBPs that are dysregulated in both Type 1 and Type 2 diabetes.